Global humanitarianism and media culture - Lawrence, Michael; Tavernor, Rachel (Humanitarianism: Key Debates and New Approaches, 2019)
There is as yet no collection that examines the longer histories of global humanitarianism and media culture, which would enable readers to consider the various continuities, as well as the differences, characterising the mass media's relationship with international humanitarian crisis and relief. This collection examines this relationship from the 1950s to the present, from Marshall Plan documentaries and the promotion of the Peace Corps in the decades following the Second World War to the role of Facebook in the work of NGOS and the media's response to the current refugee crisis. The majority of the contributors to the proposed volume are specialists in the fields of media, film and cultural studies and approach the question of humanitarianism-media culture relations from a variety of critical and theoretical perspectives, and draw on other disciplines such as sociology, journalism, politics and anthropology.